Silhouettea chaimi Goren, 1978, a junior synonym of Papillogobius melanobranchus (Fowler, 1934) (Teleostei: Gobiidae) - Kovačić, Marcelo; Bogorodsky, Sergey (Zootaxa, 2013)
The high resemblance of Silhouettea chaimi Goren, 1978 to two Papillogobius species, P. melanobranchus and P. reichei was noticed from their published descriptions. The comparison of types of S. chaimi with comparative material of P. mel-anobranchus and P. reichei confirmed the lack of morphological differences between two nominal species, S. chaimi and P. melanobranchus. Therefore, S. chaimi is placed as a junior synonym of P. melanobranchus.